S-1 Maintenance Therapy After First-Line Treatment With Nab-Paclitaxel Plus S-1 for Advanced Pancreatic Adenocarcinoma: A Real-World Study - Shi, Yan; Han, Quanli; Yan, Huan; Lv, Yao; Yuan, Jing; Li, Jie; Guan, Shasha; Wang, Zhikuan; Huang, Lei; Dai, Guanghai (Frontiers in Oncology, 2022)
Background: In our previous phase II study, nab-paclitaxel plus S-1 (NPS) showed encouraging objective response rate (ORR) as first-line treatment for advanced pancreatic adenocarcinoma (APAC). This study aimed to evaluate the effectiveness and safety of S-1 maintenance after NPS in APAC, and to explore factors predicting survival benefits when using S-1 maintenance. Methods: Between 2014 and 2018 a total of 182 patients with APAC who were primarily treated with NPS were included. For patients without progression or with treatment discontinuation due to any reasons within 4 months during NPS treatment, S-1 monotherapy was administrable as maintenance therapy at physicians’ discretion based on patients’ preference and performance status. Efficacy and safety of S-1 maintenance were investigated. Results: In 123 patients without progression within 4 months during NPS treatment, 74 received S-1 maintenance, and had median progression-free survival of 9.6 months and median overall survival of 16.7 months. Multivariable analysis showed that in patients receiving S-1 maintenance after first-line NPS therapy, ECOG Performance Status score of 0, non-metastatic disease, and complete or partial response as best response to NPS chemotherapy were independently associated with better survival. The most common all-grade hematological and non-hematological adverse events were neutropenia (82.4%) and peripheral neurotoxicity (66.2%), respectively, and the most common ≥Grade 3 hematological and non-hematological adverse events were neutropenia (40.5%) and peripheral neurotoxicity (6.8%), respectively in patients who received S-1 maintenance. Conclusions: Our real-world study showed that S-1 maintenance following NPS was effective and well-tolerated, which offers a promising alternative treatment strategy with encouraging survival for APAC.